PENGEMBANGAN MODEL PEMBELAJARAN SINEKTIK DI MADRASAH IBTIDAIYAH - Rofiatul Hosna (Jurnal Pendidikan Islam, 2013)
The purpose of this study is to produce synectic learning model in order to develop students' creative thinking skills in teaching Social Studies in the Madrasah Ibtidaiyah. This research was conducted using research and development approach. Validation testing was performed in five madrasas of which the qualification are considered good, moderate and less. This study was developed by doing experiments and comparing between Synectic Learning Model (KE) and Conventional Model KK). Validation test results indicated that students' ability to think creatively was different between the test results of the experimental group (α ≤ .0001) and the control group (α ≤ .0001). The result of this study concluded that: 1) Synectic Learning Model is the learning model proposed by Gordonsynectic. The development and modifications were made based on the condition and capability of students in the l Environtment of Elementary Madrasah; 2) The Implementation of synectic learning model can improve learning conditions on the subjects of Social Studies in Elementary Madrasah; 3) synectic learning model is effective to enhance creative thinking skills and student learning outcomes on the subjects of Social Sciences, as well as improving teacher performance.